POSISI STRATEGIS INDONESIA DALAM PERDAGANGAN ASEAN: SEBUAH TINJAUAN EKONOMI POLITIK INTERNASIONAL - Hilmi Rahman Ibrahim (Universitas Nasional, 2017)
Regionalism in international relations has been a contemporary phenomenon since the world entered its 20th century. In Southeast Asia, Indonesia as one member of ASEAN has managed consolidating the country’s position in trade cooperation and competition. With setting up its economic community of MEA in 2015, ASEAN has focused on trade sector cooperation. Given the strategic position of Indonesia where two third of ASEAN demands for goods and services are supplied by Indonesia, the setting up of ASEAN economic community (MEA) is crucial for individual members to compete and cooperate. How would Indonesia take this opportunity? The paper discusses the factors that need more attention in such areas as government regulation, technology, competitiveness, and innovation. While natural resources and Indonesia’s strategic position in terms of geography and trade route are there to exist, those factors will determine whether Indonesia will be the winner or the loser. Keywords : regionalism, strategic factors, cooperation, competition, competitiveness.